Interactions between Melanin Enzymes and Their Atypical Recruitment to the Secretory Pathway by Palmitoylation - Upadhyay, Srijana (mBio, 2016)
Melanins are biopolymers that confer coloration and protection to the host organism against biotic or abiotic insults. The level of protection offered by melanin depends on its biosynthesis and its subcellular localization. Previously, we discovered that Aspergillus fumigatus compartmentalizes melanization in endosomes by recruiting all melanin enzymes to the secretory pathway. Surprisingly, although two laccases involved in the late steps of melanization are conventional secretory proteins, the four enzymes involved in the early steps of melanization lack a signal peptide or a transmembrane domain and are thus considered “atypical” secretory proteins. In this work, we found interactions among melanin enzymes and all melanin enzymes formed protein complexes. Surprisingly, the formation of protein complexes by melanin enzymes was not critical for their trafficking to the endosomal system. By palmitoylation profiling and biochemical analyses, we discovered that all four early melanin enzymes were strongly palmitoylated during conidiation. However, only the polyketide synthase (PKS) Alb1 was strongly palmitoylated during both vegetative hyphal growth and conidiation when constitutively expressed alone. This posttranslational lipid modification correlates the endosomal localization of all early melanin enzymes. Intriguingly, bioinformatic analyses predict that palmitoylation is a common mechanism for potential membrane association of polyketide synthases (PKSs) and nonribosomal peptide synthetases (NRPSs) in A. fumigatus. Our findings indicate that protein-protein interactions facilitate melanization by metabolic channeling, while posttranslational lipid modifications help recruit the atypical enzymes to the secretory pathway, which is critical for compartmentalization of secondary metabolism.